Empowerment of Business Owners and Baristas through Digital Marketing Program at Kopi Johar Yogyakarta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Human resources are one of the critical factors in the success of a coffee business in the digital era. Therefore, quality education and training are needed to improve business owners' and baristas' skills and knowledge. This research aims to empower business owners and baristas at Kopi Johar Yogyakarta through a digital marketing program. The objectives of this study are to improve the quality of human resources at Kopi Johar, understand the role of education in empowering business owners and baristas, and measure their knowledge of effective digital marketing strategies. The method used in this research is qualitative methods and descriptive , with data collection techniques through observation and in-depth interviews. The results showed that business owners and baristas at Kopi Johar require upgraded digital marketing skills. While they have a basic understanding of coffee culture and customer service, there is a significant need for further development in terms of digital marketing. This is evident from the high interest in the digital marketing training program and active participation in the training sessions. On the positive side, the trainees demonstrated improved skills in creating engaging digital content and online marketing strategies, potentially increasing Kopi Johar's visibility and sales in the future.